Christian-Muslim relations. - Thomas, David 1948-; Mallett, Alexander. (The History of Christian-Muslim Relations, 2017)
Christian-Muslim Relations, a Bibliographical History 9 (CMR 9) covering Western and Southern Europe in the period 1600-1700 is a further volume in a general history of relations between the two faiths from the seventh century to the early 20th century. It comprises a series of introductory essays and also the main body of detailed entries which treat all the works, surviving or lost, that have been recorded. These entries provide biographical details of the authors, descriptions and assessments of the works themselves, and complete accounts of manuscripts, editions, translations and studies. The result of collaboration between numerous leading scholars, CMR 9, along with the other volumes in this series is intended as a basic tool for research in Christian-Muslim relations. Section Editors: Clinton Bennett, Luis F. Bernabé Pons, Jaco Beyers, Karoline Cook, Lejla Demiri, Martha Frederiks, David D. Grafton, Stanisław Grodź, Alan Guenther, Emma Loghin, Gordon Nickel, Claire Norton, Reza Pourjavady, Douglas Pratt, Radu Păun, Peter Riddell, Umar Ryad, Mehdi Sajid, Cornelia Soldat, Karel Steenbrink, Davide Tacchini, Ann Thomson, Carsten Walbiner.